Investigation of the mechanical properties of electrodeposited nickel and magnetron sputtered chromium nitride coatings deposited on mild steel substrate - Bhatti, J.; Fazal, M.A.; Khan, A.F.; Bushroa, Abdul Razak; Quazi, M.M. (Taylor & Francis, 2016)
Electrodeposition and magnetron sputtering techniques have been employed for the deposition of Ni and bilayer NiCrN coatings, respectively, on mild steel substrate. Ni electrodeposition was performed using sulfate Watt’s bath, while magnetron sputtering was performed on electrodeposited Ni using DC power 350 W and base pressure of 3 × 10−5 Torr in order to prepare bilayer NiCrN coatings. Structural and mechanical properties of Ni and bilayer NiCrN coatings have been investigated using various characterization techniques such as SEM-EDX, XRD, hardness, adhesion testing, etc. SEM analysis reflects the formation of spherical/nodular particles of varying sizes in NiCrN coating whereas Ni coating shows irregular, agglomerated, and non-uniform distribution of particles. Formation of hard CrN phase in NiCrN coating has been confirmed by XRD and EDX. NiCrN coating exhibits better hardness in comparison with Ni coating due to the formation of nitride phase. Micro scratch testing of bilayer NiCrN coating shows better interlayer adhesion and adhesion with mild steel substrate. The combination of electrodeposition and magnetron sputtering can produce inexpensive NiCrN coating containing hard CrN phase with better mechanical properties for automotive applications.